Nano-precipitates in severely deformed and low-temperature aged CoCrFeMnNi high-entropy alloy studied by synchrotron small-angle X-ray scattering. (February 2019) - Huang, Yung-Chien; Tsao, Cheng-Si; Wu, Shyi-Kaan; Lin, Chieh; Chen, Chih-Hsuan
Abstract: The synchrotron small-angle X-ray scattering (SAXS) technique was used to reveal the evolution and growth kinetics of nano-precipitates (ppts) of severely cold-rolled CoCrFeMnNi high-entropy alloy aged at 350–500 °C for different times. The nano-ppts in the as cold-rolled alloy have a radius of ∼1.2 nm, grow drastically in the early 30 min of aging at 500 °C, and reach the saturation stage at 60 min aging. The rapid increase in the size/volume fraction of the nano-ppts with the aging time is also quantitatively correlated with significant precipitation hardening, as indicated by measurements of the corresponding hardness and tensile stress-strain curve. TEM observation of the specimen aged at 500 °C for 60 min reveals many homogeneously distributed nano-ppts in the matrix, which have a radius of 2.0–2.5 nm. Graphical abstract: Highlights: Existence of nano-precipitates with radius of ∼1.2 nm in as severely cold-rolled CoCrFeMnNi HEA. Evolution of nano-precipitates in terms of the size and volume fraction studied by synchrotron SAXS. Growth kinetics of nano-precipitates correlated with the alloy's hardness and tensile stress-strain curve, indicating the precipitation hardening. The nano-precipitates observed by HRTEM exhibit the homogeneous distribution.